Comparison of pain-reducing effect between topical ethyl chloride spray versus subcutaneous 1% lidocaine injection during two rods system contraceptive implant insertion: A randomized controlled trial - Decha Saechoen; Srisuda Songthamwat; Taniya Manosomrit; Nitaya Chinsri; Ueamporn Summart; Metha Songthamwat (Elsevier, 2022)
Objective: To compare the effectiveness of topical ethyl chloride spray (ECS) and subcutaneous 1% lidocaine injection (LI) to reduce pain during the two rods system insertion. Materials and methods: One hundred and ten women, who underwent two rods contraceptive implant insertion during January 2021 to July 2021, were enrolled and randomly allocated to ECS and 1% LI groups. After the skin was sterilized, the assigned anesthetic method was administered before insertion of two rods contraceptive implant using the standard procedure. Pain levels during; (1) the administering of the anesthetic, (2) the insertion of the implant, (3) at 20 min after insertion and (4) overall pain levels, were evaluated, using a 10 levels visual analogue scale (VAS). Results: All basic clinical characteristics between the two groups showed no significant difference. Mean VAS during anesthetic in the ECS group were significantly lower than in the LI group (3.92 and 2.89, mean difference −1.03, 95%CI −1.76 to −0.31, p < 0.01). However, the mean VAS during; (1) implant insertion, (2) 20 min after implant insertion and (3) overall pain, in the ECS group were significantly higher than in the LI group (4.83, 1.61, 3.11 versus 0.98, 0.09, 1.66) (mean difference 3.85, 1.52, 1.44 (95%CI 3.12 - 4.58, 1.13 - 1.92, 0.97 - 1.92, p < 0.01)). Conclusion: ECS should not be used solely as an anesthetic option for the two rods system of implant insertion. It provides for less pain during the administering of the anesthetic but significantly less analgesic effect than LI.